2019
DOI: 10.1111/dpr.12386
|View full text |Cite
|
Sign up to set email alerts
|

Bureaucratic manoeuvres and the local politics of climate change mitigation in China and India

Abstract: This article explores how strategies of thinking and working politically are used by agencies within developing country governments to influence wider government agendas. It uses research on climate change mitigation in China and India to explore how government agencies seek to overcome challenges of limited capacity and competing priorities by bundling climate change together with more immediate priorities and thereby developing a coalition with an interest in achieving these objectives. The article is based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Such 'co-benefits' have been identified as crucial in motivating climate action as they bring with them immediate benefits, such as development or welfare, which local actors are familiar with and directly benefit from. In addition, local actors are more likely to have entrenched incentives to address these "co-benefits" to climate action, therefore leading to the sustained occurrence of actors "bundling" local concerns and immediate priorities with climate mitigation and adaptation objectives (Aggarwal, 2013;Cook and Chu, 2018;Harrison and Kostka, 2018;Koehn, 2008). This bundling is of particular relevance to decision-makers in the global South who are seeking to find ways to respond to climate change, but whose development and welfare concerns can overwhelm explicit climate objectives (Bhardwaj et al, 2019).…”
Section: Urban Governance Of Climate Change: the Politics Of Addressimentioning
confidence: 99%
See 1 more Smart Citation
“…Such 'co-benefits' have been identified as crucial in motivating climate action as they bring with them immediate benefits, such as development or welfare, which local actors are familiar with and directly benefit from. In addition, local actors are more likely to have entrenched incentives to address these "co-benefits" to climate action, therefore leading to the sustained occurrence of actors "bundling" local concerns and immediate priorities with climate mitigation and adaptation objectives (Aggarwal, 2013;Cook and Chu, 2018;Harrison and Kostka, 2018;Koehn, 2008). This bundling is of particular relevance to decision-makers in the global South who are seeking to find ways to respond to climate change, but whose development and welfare concerns can overwhelm explicit climate objectives (Bhardwaj et al, 2019).…”
Section: Urban Governance Of Climate Change: the Politics Of Addressimentioning
confidence: 99%
“…As case studies of climate action have shown, identifying 'win-wins' between development and climate change can motivate responses (Fisher, 2012;Khosla and Bhardwaj, 2018). However, actions to simultaneously address climate and existing objectives, with entrenched practices, need not always be win-win, and can create perverse incentives, or reinforce unjust planning, development, and decision-making practices (Chu, 2018;Harrison and Kostka, 2018).…”
Section: Urban Governance Of Climate Change: the Politics Of Addressimentioning
confidence: 99%
“…As more data and cases are reported, there is wider acceptance of the complexity of the climate policymaking process and its implementation. Unlike oversimplified models of topdown or bottom-up decision making, Harrison and Kostka (2012) found the power of bargaining and collaboration between the local and central government:…”
Section: 'Policy Bundling' or 'Policy Reinterpretation'?mentioning
confidence: 96%
“…The first set of challenges was due to the divergence between the priorities of the sub-national and national government (or local-central relationship). Although the national government was responsible for mainstreaming climate change mitigation and adaptation into the national development strategy, it was the sub-national government or local government that would turn these national policies into reality (Harrison and Kostka 2012;Teng 2012). The conflict between the two is hardly news.…”
Section: Chinese Renewable Energy Development and Policy Implementationmentioning
confidence: 99%
See 1 more Smart Citation